Knowledge, attitude and practices of the university students about COVID-19 during the Luzon lockdown in the Philippines - Jomell Miranda Santiago; Angelo Reyes Santos (International Journal of Public Health Science (IJPHS), 2021)
The Philippines is one of the many countries around the world that imposed lockdowns to stop the transmission of coronavirus disease 2019 (COVID-19). During the lockdown period, the Department of Health carried out a massive information dissemination campaign about COVID-19. Thus, the researchers want to determine the knowledge, attitude and practices of the students about the COVID-19 during the Luzon lockdown. A descriptive research design and purposive sampling were used. A questionnaire was utilized to collect data composed of the profile, questions regarding their knowledge, attitude and practice towards COVID-19 and their source of knowledge. Permission to conduct and informed consent was obtained. Data were analyzed using various statistical tools. The majority of the respondents had well to very good knowledge of COVID-19 and their source of knowledge was mainly from television and the internet. They also had a very positive attitude and they practice the different ways to prevent COVID-19. The difference between their gender and family income to their knowledge about COVID-19 was significant. Therefore, an intensified campaign should be done to reach those individuals who have limited access to television and the internet and help them to have a positive attitude and correct practices towards COVID-19.